Interferensi Gramatikal Bahasa Indonesia dalam MahÄrah KalÄm Santriwati KMI Pondok Modern Ar-Risalah Ponorogo - Ni'mah, Jauharotun (LISANIA: Journal of Arabic Education and Literature, 2018)
Language plays an important role in human life. language and humans can not be separated. Humans in all their activities need language to communicate with other humans. Communication has various kinds, one of which is oral communication that can cause interference. This research is descriptive in qualitative form. In this study the author uses listening method, the basic technique is "Tapping Technique". The advanced technique IÂ  is checking out the free involvement technique or "SBLC". Advanced technique II is a note-taking technique. Another technique is interview. The emphasis of the analysis in this study is the grammatical interference of Bahasa IndonesiaÂ  in mahÄrah kalÄm, of female students (santriwati) of Kulliyatul Muâ€™allimat Al-Islamiyah (KMI) at Ar-Risalah International Program of modern boarding school Ponorogo. Based on the emphasis of the analysis above, the authors chose the intralingual equivalent method as an analysis method. The presentation method of the data results analysis used in this study is an informal method. The results show that the form of Interference that occurs in the study location is in the form of morphological and syntactic interference. As for the factor underlying the interference in mahÄrah kalÄm of Santriwati at KMI Ar-Risalah boarding school is the difference in the system of first language or second language (interlingual transfer), analogy (excessive equation), thinness of user loyalty to recipient languages, the need for synonyms and transfer language because it brings habits in mother tongue.